Thymectomy in ocular myasthenia gravis before generalization results in a higher remission rate. (19th October 2019) - Li, Feng; Li, Zhongmin; Chen, Yanli; Bauer, Gero; Uluk, Deniz; Elsner, Aron; Swierzy, Marc; Ismail, Mahmoud; Meisel, Andreas; Rückert, Jens-C
Abstract: : OBJECTIVES: This study aimed to compare the outcomes of patients with ocular myasthenia gravis (OMG) who underwent thymectomy before generalization with the outcomes of those who underwent thymectomy after generalization. METHODS: We retrospectively reviewed patients who underwent robotic thymectomy for myasthenia gravis between January 2003 and February 2018. Patients who presented with purely ocular symptoms at myasthenia gravis onset were eligible for inclusion. Exclusion criteria were patients who were lost to follow-up and patients who underwent re-thymectomy. Patients with OMG who developed generalization before thymectomy were categorized into gOMG group and those who did not were categorized into OMG group. The primary outcome was complete stable remission according to the Myasthenia Gravis Foundation of America Post-Intervention Status (MGFA-PIS). RESULTS: One hundred and sixty-five (66 males and 99 females) out of 596 patients with myasthenia gravis were eligible for inclusion. Of these, there were 73 and 92 patients undergoing thymectomy before and after the generalization of OMG, respectively. After propensity score matching, a data set of 130 patients (65 per group) was formed and evaluating results showed no statistical differences between the 2 groups. The estimated cumulative probabilities of complete stable remission at 5 years were 49.5% [95% confidence interval (CI) 0.345–0.611] in the OMG group and 33.4% (95% CI 0.176–0.462) in the gOMG group ( P = 0.0053). Similar results were also found in patients with non-thymomatous subgroup [55 patients per group, OMG vs gOMG, 53.5% (95% CI 0.370–0.656) vs 28.9% (95% CI 0.131–0.419), P = 0.0041]. CONCLUSIONS: Thymectomy in OMG before generalization might result in a higher rate of complete stable remission than thymectomy after generalization.